Exploring the Effects of Yoga Therapy on Heart Rate Variability and Patient-Reported Outcomes After Cancer Treatment: A Study Protocol. (April 2022) - Brunet, Jennifer; Wurz, Amanda; Hussien, Julia; Pitman, Anne; Conte, Ellen; Ennis, Julie K.; Herry, Christophe L.; Seely, Andrew J. E.; Seely, Dugald
Background: Following cancer treatment, adults commonly report worsened patient-reported outcomes (PROs) such as anxiety, stress, depression, persistent and upsetting cognitive complaints, unrelenting fatigue, and reduced quality of life. Poorer PROs are associated with disrupted autonomic nervous system functioning as measured by heart rate variability (HRV), both of which have been associated with greater morbidity and mortality. Interventions to improve HRV and PROs among adults following cancer treatment are needed. Yoga therapy holds promise as an intervention to improve HRV and PROs. Therefore, we conducted a single-subject exploratory experimental study to investigate the effects of yoga therapy on HRV and specific PROs (ie, cancer-related fatigue, anxiety, cognitive function, depression, stress, quality of life) in adults treated for cancer. To reduce publication bias, improve reproducibility, and serve as a reference for forthcoming reporting of study results, we present the study protocol for this study herein. Methods: Participants were adults who completed cancer treatment that were recruited from the Ottawa Integrative Cancer Centre. Consenting and eligible participants received one 1:1 yoga therapy session (ie, 1 participant, 1 Yoga Therapist) and 6 weekly group-based yoga therapy sessions (ie, 2-3 participants, 1 Yoga Therapist). Participants completed assessments 7 times: 3 times prior to the program (ie, −6 weeks, −3 weeks, immediately prior to the 1:1 yoga therapy session), immediately following the 1:1 yoga therapy session, prior to the first group-based yoga therapy session, after the last group-based yoga therapy session, and at a 6-week follow-up. Hierarchical linear modeling will be used to test the average effects of the yoga therapy program across participants. Discussion: This study will explore several novel hypotheses, including whether yoga therapy can improve HRV and/or specific PROs among adults treated for cancer acutely (ie, during a 1:1 yoga therapy session) and/or through repeated exposure (ie, after completing 6 weeks of group-based yoga therapy). Although the findings will require confirmation or refutation in future trials, they may provide initial evidence that YT may benefit adults treated for cancer. Trial registration: ISRCTN registry, ISRCTN64763228. Registered on December 12, 2021. This trial was registered retrospectively. URL of trial registry record:https://www.isrctn.com/ISRCTN64763228